Possible healthcare-associated transmission as a cause of secondary infection and population structure of Staphylococcus aureus isolates from two wound treatment centres in Ghana. (September 2016) - Kpeli, G.; Darko Otchere, I.; Lamelas, A.; Buultjens, A.; Bulach, D.; Baines, S.L.; Seemann, T.; Giulieri, S.; Nakobu, Z.; Aboagye, S.Y.; Owusu-Mireku, E.; Pluschke, G.; et al.
Abstract: We have previously shown that secondary infections of Buruli ulcer wounds were frequently caused by Staphylococcus aureus. To gain understanding into possible routes of secondary infection, we characterized S. aureus isolates from patient lesions and surrounding environments across two Ghanaian health centres. One hundred and one S. aureus isolates were isolated from wounds ( n = 93, 92.1%) and the hospital environment ( n = 8, 7.9%) and characterized by the spa gene, mecA and the Panton–Valentine leucocidin toxin followed by spa sequencing and whole genome sequencing of a subset of 49 isolates. Spa typing and sequencing of the spa gene from 91 isolates identified 29 different spa types with t355 (ST152), t186 (ST88), and t346 dominating. Although many distinct strains were isolated from both health centres, genotype clustering was identified within centres. In addition, we identified a cluster consisting of isolates from a healthcare worker, patients dressed that same day and forceps used for dressing, pointing to possible healthcare-associated transmission. These clusters were confirmed by phylogenomic analysis. Twenty-four (22.8%) isolates were identified as methicillin-resistant S. aureus and lukFS genes encoding Panton–Valentine leucocidin were identified in 67 (63.8%) of the isolates. Phenotype screening showed widespread resistance to tetracycline, erythromycin, rifampicin, amikacin and streptomycin. Genomics confirmed the widespread presence of antibiotic resistance genes to β-lactams, chloramphenicol, trimethoprim, quinolone, streptomycin and tetracycline. Our findings indicate that the healthcare environment probably contributes to the superinfection of Buruli ulcer wounds and calls for improved training in wound management and infection control techniques.